2021
DOI: 10.5194/acp-21-7863-2021
|View full text |Cite
|
Sign up to set email alerts
|

Himawari-8-derived diurnal variations in ground-level PM<sub>2.5</sub> pollution across China using the fast space-time Light Gradient Boosting Machine (LightGBM)

Abstract: Abstract. Fine particulate matter with a diameter of less than 2.5 µm (PM2.5) has been used as an important atmospheric environmental parameter mainly because of its impact on human health. PM2.5 is affected by both natural and anthropogenic factors that usually have strong diurnal variations. Such information helps toward understanding the causes of air pollution, as well as our adaptation to it. Most existing PM2.5 products have been derived from polar-orbiting satellites. This study exploits the use of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(39 citation statements)
references
References 60 publications
0
39
0
Order By: Relevance
“…Since the Himawari‐8 satellite cannot cover Xinjiang, China (Song et al., 2021; Wei, Li, Pinker, et al., 2021), China’s second‐generation geostationary meteorological satellite FY‐4A successfully launched on 11 December 2016, can cover the entire territory of China. Its Advanced Geosynchronous Radiation Imager (AGRI) imager can provide multi‐band full‐disk images with a time resolution of 15 min (Y. Chen et al., 2020; Mao et al., 2021; Zhang, Zhu, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Himawari‐8 satellite cannot cover Xinjiang, China (Song et al., 2021; Wei, Li, Pinker, et al., 2021), China’s second‐generation geostationary meteorological satellite FY‐4A successfully launched on 11 December 2016, can cover the entire territory of China. Its Advanced Geosynchronous Radiation Imager (AGRI) imager can provide multi‐band full‐disk images with a time resolution of 15 min (Y. Chen et al., 2020; Mao et al., 2021; Zhang, Zhu, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2017a) established a GRNN (generalized regression neural network) model for the whole of China to estimate PM 2.5 concentration, and the results demonstrated that the performance of the deep learning model was better than that of the traditional linear model. In addition, there are some novel algorithms such as the space-time extra-tree (STET) (Wei et al, 2021b) and space-time random forest (STRF) (Wei et al, 2019a) algorithms that are also used for PM 2.5 inversion research.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various algorithms such as extreme gradient boost (XGBoost) and light gradient boost machine (LightGBM) have been developed to overcome the shortcomings of GBM. XGBoost [18,19] and LightGBM [20][21][22] have been used in studies on PM prediction model development and demonstrated a relatively good prediction performance compared to the GBM model. However, only a few studies have applied LightGBM, a relatively new algorithm, and comparative studies between boosting algorithms are scarce.…”
Section: Introductionmentioning
confidence: 99%